SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN MAHASISWA BERPRESTASI MENGGUNAKAN METODE SIMPLE ADDITIVE WEIGHTING (SAW) - Kiki Yasdomi; Mi'rajul Rifqi; Hendri Maradona; Hary Kurniawan (RJOCS (Riau Journal of Computer Science), 2019)
Technology at this time is very important for everyday people, computerization is needed to facilitate human work. In the education sector, especially at the Pasir Pengaraian University (UPP). UPP is a university located in Kab. Rokan Hulu, Riau, UPP has problems in processing data on the selection of outstanding students (PILMAPRES) using Microsoft Excel which is considered to have many shortcomings. The purpose of this study was to implement a decision support system for the selection of outstanding students. This system will be implemented using the PHP and MySQL programming languages. Decision support systems that are made using the Simple Additive Weighting (SAW) method, using the interview method to collect data. The results of the study show that the adoption of a decision support system using the Simple Additive Weighting (SAW) method can recommend the best alternatives to pilmpares UPP